2015
DOI: 10.1080/17588928.2015.1070136
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and implicit attention to social threat: A high-performance electrical neuroimaging study

Abstract: Prior research has suggested that loneliness is associated with an implicit hypervigilance to social threats-an assumption in line with the evolutionary model of loneliness that indicates feeling socially isolated (or on the social perimeter) leads to increased attention and surveillance of the social world and an unwitting focus on self-preservation. Little is known, however, about the temporal dynamics for social threat (vs. nonsocial threat) in the lonely brains. We used high-density electrical neuroimaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 63 publications
7
93
0
Order By: Relevance
“…Overall, previous studies report the strongest associations between loneliness and either Extraversion or Neuroticism (Atak, ; J. T. Cacioppo et al, ; Lopes et al, ; Mund & Neyer, ; Stephan, Fäth, & Lamm, ; Teppers et al, ; Vanhalst et al, ), which is theoretically plausible. In behavioral and neuroimaging research, loneliness is characterized by an implicit sensitivity to negative social stimuli (J. T. Cacioppo et al, ; J. T. Cacioppo, Norris, Decety, Monteleone, & Nusbaum, ; S. Cacioppo, Balogh, & Cacioppo, ; S. Cacioppo et al, ; Duck, Pond, & Leatham, ) and a decreased sensitivity to positive social stimuli (J. T. Cacioppo et al, ; J. T. Cacioppo & Patrick, ). Neuroticism is characterized by a heightened sensitivity to negative stimuli overall, whereas Extraversion is characterized by a heightened sensitivity to especially social positive stimuli (Larsen & Ketelaar, ; Rusting & Larsen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, previous studies report the strongest associations between loneliness and either Extraversion or Neuroticism (Atak, ; J. T. Cacioppo et al, ; Lopes et al, ; Mund & Neyer, ; Stephan, Fäth, & Lamm, ; Teppers et al, ; Vanhalst et al, ), which is theoretically plausible. In behavioral and neuroimaging research, loneliness is characterized by an implicit sensitivity to negative social stimuli (J. T. Cacioppo et al, ; J. T. Cacioppo, Norris, Decety, Monteleone, & Nusbaum, ; S. Cacioppo, Balogh, & Cacioppo, ; S. Cacioppo et al, ; Duck, Pond, & Leatham, ) and a decreased sensitivity to positive social stimuli (J. T. Cacioppo et al, ; J. T. Cacioppo & Patrick, ). Neuroticism is characterized by a heightened sensitivity to negative stimuli overall, whereas Extraversion is characterized by a heightened sensitivity to especially social positive stimuli (Larsen & Ketelaar, ; Rusting & Larsen, ).…”
Section: Introductionmentioning
confidence: 99%
“…In an early fMRI study, Cacioppo, Norris, Decety, Monteleone and Nusbaum () found that lonely people have greater activation in the visual cortex when viewing unpleasant social pictures of people than objects. Two recent EEG studies extended that work and demonstrated that lonely people detect and process social threat more quickly than non‐lonely people when tasks were presented using words (Cacioppo, Balogh & Cacioppo, ) and images (Cacioppo, Bangee, Balogh, Cardenas‐Iniguez, Qualter & Cacioppo, ). Such findings suggest that lonely people show automatic and implicit hypervigilance to social threats in the brain.…”
Section: Introductionmentioning
confidence: 71%
“…The tools of social neuroscience make it possible to approach loneliness not only by the analysis of subjective self-reports (e.g., UCLA loneliness scale), but also by approaching the automatic (non-conscious) self-preservation mechanisms of loneliness, for instance, using high performance electrical neuroimaging and evoked microstate analyses [13-14]. In lonely individuals, recent studies have shown that the perception of social threat (compared to non-social threat) activates the para-hippocampal and amygdala regions during the early (non-conscious) period (between 116 ms and 136 ms) of information processing [13-14], and the amygdala region (including BNST) modulates the neural responses to social stimuli in the temporo-parietal junction [14].…”
Section: Testing the Hypothesismentioning
confidence: 99%
“…The tools of social neuroscience make it possible to approach loneliness not only by the analysis of subjective self-reports (e.g., UCLA loneliness scale), but also by approaching the automatic (non-conscious) self-preservation mechanisms of loneliness, for instance, using high performance electrical neuroimaging and evoked microstate analyses [13-14]. In lonely individuals, recent studies have shown that the perception of social threat (compared to non-social threat) activates the para-hippocampal and amygdala regions during the early (non-conscious) period (between 116 ms and 136 ms) of information processing [13-14], and the amygdala region (including BNST) modulates the neural responses to social stimuli in the temporo-parietal junction [14]. In turn, loneliness is known to be inversely related to the level of activation of the temporo-parietal region bilaterally in response to social threat (compared to non-social threat notably between 116 ms and 124 ms post-stimulus onset; [14]), possibly reflecting a disorder in reading others' intentions, feelings, and others' behaviours or a less focus on others and more on one's own self-preservation in negative social contexts [5, 14, 92].…”
Section: Testing the Hypothesismentioning
confidence: 99%
See 1 more Smart Citation